Effect of Saline Irrigation on Agro-Physiological and Biochemical of Some Quinoa Cultivars Under Field Conditions - Moatz A. Mohamed; M.H. Mubarak; Salah.A. Okasha (Journal of Agronomy Research, 2019)
In regions where irrigation water supplies are limited, drainage or water with salinity can be used to supplement them. Field experiments were carried out during the quinoa growing season of 2015/2016 and 2016/2017 at North Sinai in order to evaluate six quinoa genotypes (Chenopodium quinoa Willd.) under saline irrigation (5400 ppm) on growth, yield, its component, seeds chemical composition under field conditions. For plot 50% heading and maturity, the most earliness averages were 47.25 and 92.50 day, respectively for genotype Q-Q37-1, while the least earliness averages were 55.75 and 96.25 for genotypes KVLSRA 2 and KVLSRA 1, respectively. The highest averages was recorded for number of panicles/plant, plant fresh weight, plant yield weight, harvest index, 1000 seeds weight index and yield / fed-1 (ton) were 12.27, 82.32 gm, 17.83 gm, 28.89 %, 2.97 gm and 1.84 ton fed-1 ) for genotypes Q-Q37-1, Q-Q37-1, Q-Q37-1, Q-Q37-1, Q52 and Q-Q37-1, respectively. While, the lowest values were recorded for genotypes KVLSRA1, KVLSRA1, KVLSRA1, Regeolona, KVLSRA1 and KVLSRA1 with averages 8.72, 23.73gm, 5.52 gm, 22.76 %, 2.43 gm and 1.23 ton fed-1, respectively. For protein and carbohydrates total content, values ranged from 14.75 to 10.59 and from 58.13 to 54.64 % for genotypes Q52 and Regeolona, respectively. While in moisture content, values ranged from 11.66 to 10.83 for genotypes KVLSR1 and Q-Q37-1 , respectively. Also, fats content ranged from 10.44 to 7.14 % for genotypes Q52 and Regeolona, respectively. While values of saponin ranged from 0.56 to 0.37% for genotypes KVLSR1 and Regeolona, respectively.
Keywords: Quinoa